Intravenous immunoglobulin for acute exacerbation of fibrotic idiopathic interstitial pneumonias: IV immunoglobulin for acute exacerbation of fibrotic IIPs - Higo, Hisao; Ichikawa, Hirohisa; Nakamura, Naoki; Fujii, Masanori; Matsuoka, Katsuhiro; Seki, Shoko; Wada, Takamasa; Suzaki, Noriyuki; Nagata, Takuya; Arakawa, Yukako; Mori, Yoshihiro; Marukawa, Masaomi; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background and aim: Acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is a fatal condition with no established treatment. Intravenous immunoglobulin (IVIG) is a unique therapy with both anti-inflammatory and anti-infective effects. Therefore, we hypothesized that IVIG may have a positive effect on AE of interstitial pneumonia. This study aimed to determine the effect of IVIG in patients with AE of fibrotic idiopathic interstitial pneumonias (IIPs), including IPF. Methods: We retrospectively analyzed consecutive patients who were diagnosed with AE of fibrotic IIPs and treated with pulse corticosteroid therapy (methylprednisolone 500–1000 mg/day for 3 days) between April 2018 and May 2021 at Kagawa Rosai Hospital and KKR Takamatsu Hospital. Results: This study included 52 patients with AE of fibrotic IIPs (IPF,41; fibrotic IIPs other than IPF,11). Thirteen patients received IVIG (5 g/day for 3–5 days) concurrently with pulse corticosteroid therapy. The remaining 39 patients were assigned to the control group. The survival rate on day 90 was significantly higher in the IVIG group than that in the control group (76.9% vs. 38.5%, p = 0.02). IVIG administration (odds ratio [OR], 0.11; 95% confidence interval [CI], 0.02–0.69; p = 0.02) and C- reactive protein (OR, 1.19; 95% CI, 1.06–1.33, p < 0.01) were independently associated with 90-day mortality. Conclusions: The results indicate that administration of IVIG may improve the survival of patients with AE of fibrotic IIPs. We are now conducting a prospective study to confirm the effect of IVIG on AE of IPF since May 2022 (jRCT1061220010).